Longstanding Eosinophilic Gastroenteritis of More Than 20 Years - Hugh J Freeman (Canadian Journal of Gastroenterology)
Eosinophilic gastroenteritis (EGE) is an eosinophil-predominant inflammatory process that may be detected in endoscopic gastric or intestinal biopsies. The long-term natural history and effects of EGE treatment are not known. A 44-year-old man with abdominal pain was treated with oral ketotifen and followed for more than 20 years. Ketotifen provided symptomatic benefit, with prompt clinical relapse if the drug was discontinued. However, despite the use of ketotifen, the endoscopic abnormalities persisted and appeared to progress. Gastric body and antral mucosal folds appeared thickened, erythematous and friable, with minimal erosive change. Later, even during long asymptomatic periods suggesting clinical ‘remission’, inflammatory polypoid change, previously described in children with EGE, developed with mucosal ‘pock-marking’ and apparent scarring. Ketotifen treatment does not appear to prohibit or reverse the inflammatory process in the gastric mucosa in EGE, although long-term effects of steroids may be avoided. In the future, treatment of EGE may involve monoclonal antibody agents that target the specific biological effects of the eosino-phil, apparently central to this unusual inflammatory process.